Youth and Culture in Namibia - Maree, Maretha (1998)
BACKGROUND ON NAMIBIA Namibia is the last colony in Africa to attain Independence. The Republic of Namibia, lying across the Tropic of Capricorn, has a population of about 1.8 million and covers an area of 824.292 sq km. It is bordered by South Africa in the south, by Botswana on the east and Angola on the north, while the narrow Caprivi Strip in north east extends Namibia's borders to the Zambezi river and a short border with Zambia. The name Namibia was officially adopted by the United Nations in 1968. lt replaced the colonial name of ' South West Africa'. The name derives from one of the oldest deserts in the world, the Namib. The desert forms a narrow plain 65-16km wide and extending 1 600km along the coast, separating the rest of the country from the south Atlantic Ocean. The fine sand of Namib forming huge sand dunes cover one fifth of the country. Namibia's major resource, diamond and uranium, is to be found in the fine sand of the Namib desert. However, the area is almost devoid of vegetation and therefore near to uninhabitable. The eastern parts of Namibia is covered by a semi-desert, the Kalahari, were there is some vegetation. In Ovamboland, the northern parts ofthe Kalahari, crop cultivation is possible, due to a network of watercourses known as 'oshanas'. In between the Namib and the Kalahari deserts lie the Central Plateau with an average elevation of 11 OOm above sealeveL It covers one half of the country. "The Plateau stretching the full length of the country, is Namibia's most fertile area and thus most suitable for human settlement. In its northern parts, the Plateau is suitable mostly for cattle-rearing but also for crop cultivation on a limited scale. The southern part is much dryer, covered with shrub steppe and it is unsuitable for anything but cattle, goat and/or sheep-rearing. Average annual rainfall is 270mm and droughts are frequent. Namibia has the driest climate south of Sahara." (Strand: 1991 ). The implication of the above mentioned is that vineyards cannabis coca plant or opium poppies is not cultivated in Namibia, and that all substances of abuse are imported.